Characterization of different isoforms of the HIF prolyl hydroxylase PHD1 generated by alternative initiation - Tian, Ya-Min (Portland Press Ltd., 2006)
The heterodimeric transcription factor HIF (hypoxia-inducible factor) is central to the regulation of gene expression by oxygen. Three oxygen-dependent prolyl hydroxylase enzymes [PHD1 (prolyl hydroxylase domain 1), PHD2 and PHD3] control the abundance of HIF. In the presence of oxygen, they hydroxylate specific proline residues in HIF-α, allowing recognition by pVHL (von Hippel-Lindau protein) and subsequent ubiquitylation and proteasomal destruction. The precise roles and regulation of these enzymes are therefore of particular importance in understanding the physiological and pathological responses to hypoxia. In the present study, we define the existence of two species of PHD1 and provide evidence that they are generated by alternative translational initiation. We demonstrate that these alternative forms are both biologically active with similar HIF prolyl hydroxylase activity but that they differ in their responses to oestrogen, cell confluence and proteasomal inhibition. We show that the two PHD1 species are subject to proteolytic regulation but differ markedly in their protein stability. Though each isoform has the potential to interact with members of the Siah (seven in absentia homologue) ubiquitin ligase family, genetic studies indicated that other proteolytic mechanisms are responsible for control of stability under the conditions examined. The data define the existence of a further level of control in the pathway that regulates cellular responses to hypoxia.